AI-BASED PROJECT-BASED LEARNING TO IMPROVE SPEAKING SKILLS AND CONFIDENCE IN ECC - Fauzia Aysah; Waode Hamsia (LPPM Universitas PGRI Jombang, 2026)
This study aims to analyze the implementation of AI-based Project-Based Learning (PjBL) to enhance students’ speaking confidence in English. The study employed a qualitative case study design involving senior high school students aged 15–18 years participating in the English Conversation Club (ECC). Data were collected through classroom observations, semi-structured interviews, questionnaires, and documentation of students’ project videos and AI conversation transcripts. The data were analyzed using thematic analysis to identify patterns related to students’ speaking development and confidence improvement. The findings indicate that the use of AI-based PjBL contributed significantly to students’ speaking confidence by providing a supportive, interactive, and low-pressure learning environment. Students showed greater enthusiasm, improved pronunciation and fluency, and increased willingness to practice speaking English without fear of making mistakes. In addition, AI-based interaction enabled students to receive immediate feedback and to practice independently at their own pace. The study concludes that integrating AI into Project-Based Learning effectively fosters students’ speaking confidence and engagement. This research implies that AI-based PjBL can serve as an innovative approach to creating adaptive and student-centered English speaking instruction in senior high school contexts.